CITES‐listed sharks remain among the top species in the contemporary fin trade. Issue 4 (17th July 2018) - Cardeñosa, Diego; Fields, Andrew T.; Babcock, Elizabeth A.; Zhang, Huarong; Feldheim, Kevin; Shea, Stanley K. H.; Fischer, Gunter A.; Chapman, Demian D.
Abstract: Trade‐driven overexploitation threatens many sharks. Twelve of the world's most vulnerable shark species have been listed on the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) to regulate internationally traded products such as meat and dried fins. CITES records indicate that Hong Kong was the world's top legal importer of dried fins from listed sharks in 2015 ( N = 8 species at that time), but traded a relatively small volume, with a few partners, in a small number of shipments (16). In contrast two CITES Appendix II listed hammerheads were consistently the fourth and fifth most common species (out of >80) in processed fin trimmings ( N = 9, 200) collected randomly from the Hong Kong retail dried fin market from February 2014 to December 2016 and were found in 100% of sampling events and in 66% of sampled retail vendors. This difference, and the fact that exporting nations previously known to land these species were not among those to report trade to CITES, suggest that listed species were often imported without CITES documentation in 2015. There are a number of incentives for trade hubs to meet their obligations to this treaty, which they could achieve by scaling up monitoring capacity and increasing inspection efficiency.